230k views
3 votes
Susie and Amelia solved the same equation using two separate methods. Their work is shown in the table below:

User Mkarasek
by
5.6k points

1 Answer

1 vote
Stephen and Aaron solved the same equation using two separate methods. Their work is shown in the table below:

Stephen Aaron:
3x - 2 = 5x - 6 3x - 2 = 5x - 6
3x - 2 + 2 = 5x - 6 + 2 3x - 3x - 2 = 5x - 3x - 6
3x = 5x - 4 -2 = 2x - 6
3x - 5x = 5x - 5x - 4 -2 - 6 = 2x
-2x = -4 -8 = 2x
x = 2 -4 = x

Identify who made the error and what he did wrong.
Aaron made the error when he subtracted 6.

Aaron made the error when he subtracted 3x.

Stephen made the error when he added 2.

Stephen made the error when he subtracted 5x.

answer:

In the Aaron`s work:
- 2 = - 2 x - 6
and after that:
- 2 - 6 = 2 x
It should be:
- 2 + 6 = 2 x
or: - 2 + 6 = 2 x - 6 + 6
Answer:
A ) Aaron made the error when he subtracted 6.
User Garric
by
7.0k points